Minstrelsy, Blackface, and Racialized Performance in Narrative Stereoviews, 1860-1902 (International Journal on Stereo & Immersive Media, 2022)
This essay looks at the influence of blackface minstrelsy on stereoviews of British and American publication from 1860-1902, within a transatlantic perspective. Using Black and blackface models, as well as hand-coloring, or “photographic blackface”, stereoview publishers employed ready cultural codes from minstrelsy for racialized performance in order to posit an antithesis to whiteness for comic effect. Taking a “yes, it’s racist and” approach, this paper demonstrates that narrative stereoviews were informed by minstrelsy’s codes of white racial superiority and Black inferiority, and these codes could be destabilized through over-signage and contradictory or crossed signifiers. Binaries of race, gender and sexuality in the stereoviews can become unstable, while the stereoview’s two photographs contribute to this effect by offering an already doubleness that, when applied to race, suggests a relation more close than different.